A Research on Ordinary Differential Equations and Operators: Analytical Approach: Examining the Influence of Uncertainty and Variability on Ordinary Differential Equations Modeling (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Ordinary differential equations assume an imperative part in the displaying of some true procedures. To ensure dependable outcomes, display plan and examination must record for uncertainty as well as variability in the model information. The proliferation of uncertainty and variability through the model elements and their impact on the yield is contemplated by affectability examination.